Refusing invitations via email: strategy use in Turkish and American-English refusals - Merdin, Emine. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
The aim of this study is to analyze the similarities and differences between Turkish and American English in the speech acts of refusal via email. It aims to uncover Turkish and American English refusal strategies employed in emails sent to refuse invitations, and examine whether social distance between the interlocutors has an impact on strategy use by Turkish L1 speakers (TSs) and American English L1 speakers (AESs). It further investigates the content of refusals and the effect of data collection method on strategy use. To this end, the data have been collected through natural emails and discourse completion tasks (DCT) from TSs and AESs. Each refusal in the data has been coded and counted. The data have been analyzed to compare the frequencies of refusal strategies, the effect of social distance on strategy use across groups, the content of refusals, and the effect of the data collection method. PASW has been used to run descriptive statistics and repeated measures of ANOVA. The results show more similarities than differences in strategy use in Turkish and American English refusal emails. Thus, pragmatic failure might be unlikely for American learners of Turkish and Turkish learners of American English. However, the findings also reveal that there are differences that are language-specific and culturally-shaped. The findings also suggest that natural emails tend to be more elaborated in that they have more strategies, thus DCTs may not thoroughly reflect the language in use and should be complemented with methods.
Keywords: Electronic mail systems.; Electronic mail messages.